Plant reproductive strategies vary under low and high pollinator densities. Issue 8 (26th February 2018) - Mu, Junpeng; Wu, Qinggui; Yang, Yulian; Huang, Mei; Grozinger, Christina M.
Abstract : Long‐term variation in the population density of honey bees Apis mellifera across landscapes has been shown to correlate with variation in the floral traits of plant populations in these landscapes, suggesting that variations in pollinator population density and foraging rates can drive floral trait evolution of their host plants. However, it remained to be determined whether this variation in plant traits is associated with adaptive variation in plant reproductive strategies under conditions of high and low pollinator densities. Here we conducted a reciprocal transplant experiment to examine how this variation in floral traits, under conditions of either high and low pollinator density, impacted seed production in the Tibetan lotus Saussurea nigrescens . In 2014 and 2015, we recorded the floral traits, pollinator visitation rates, and seed production of S. nigrescens populations grown in both home sites and foreign sites, where sites varied in honey bee population density. Our results demonstrated that the floral traits reflected those of their original population, regardless of their current location. However, seed production varied with both population origin and transplant site. Seed number was positively correlated with flower abundance in the pollinator‐rich sites, but with nectar production in the pollinator‐poor sites. Pollinator visitation rate was also positively correlated with flower number at pollinator‐rich sites, and with nectar volume at pollinator‐poor sites. Overall, the local genotype had higher seed production than nonlocal genotypes in home sites. However, when pollen is hand‐supplemented, plants from pollinator‐rich populations had higher seed production than plants from pollinator‐poor populations, regardless of whether they were transplanted to pollinator‐rich or ‐poor sites. These results suggest that the plant genotypic differences primarily drive variation in pollinator attraction, and this ultimately drives variation in seed: ovule ratio. Thus, our results suggest that flowering plant species use different reproductive strategies to respond to high or low pollinator densities.